Estimation and prediction on the economic burden of schistosomiasis in 25 endemic countries - Xian-Fa Chen; Qin Li; Robert Bergquist; Jin-Xin Zheng; Su-Ying Guo; Qiu-Feng Lan; Zheng-Ze He; Li-Juan Zhang; Chun-Li Cao; Jing Xu; Xiao-Nong Zhou (Infectious Diseases of Poverty)
Abstract Background Schistosomiasis is a neglected tropical disease, primarily prevalent in tropical and subtropical regions. It imposes a significant health and economic burden in low- and middle-income countries, but a study of its comprehensive economic impact of the disease at the global level has not been carried out. As this is essential for evidence-based decision-making, this study aims to estimate the macroeconomic burden of schistosomiasis in 25 endemic countries. Methods We used a health-augmented macroeconomic (HAM) model, as well as observed data from 2010 to 2021 and projected data from 2022 to 2050, to model gross domestic product (GDP) under two scenarios: with and without schistosomiasis. The data were obtained from the Global Burden of Disease Study 2021 (GBD 2021), the World Bank database, the International Monetary Fund (IMF) database, the International Labour Organization (ILO) database, the United Nations Population Division's World Population Prospects 2022 database, the Barro-Lee Educational Attainment dataset, the Penn World Table (PWT) database, and relevant literature. The economic burden was quantified as the difference in GDP between these two scenarios. The HAM model considered: (i) the impact of schistosomiasis mortality and morbidity on labor supply; (ii) age and gender differences in education and work experience among schistosomiasis patients; and (iii) the impact of schistosomiasis treatment costs on physical capital accumulation. To be able to compare the purchasing power of different countries, we used international dollars (INT$), a hypothetical currency unit based on purchasing power parity. Results We estimated the macroeconomic burden of schistosomiasis in 25 schistosomiasis endemic countries was INT$ 49,504 million [uncertainty interval (UI): 48,668–50,339] for the study period, using a 3% discount rate in the main analysis. The result implies that the economic burden of schistosomiasis across these 25 countries during study period is equivalent to 0.0174% (UI: 0.0171–0.0177) of total GDP. Among all schistosomiasis-endemic countries included, Egypt had the largest absolute economic burden (INT$ 11,400 million, UI: 11,221–11,578), followed by Brazil (INT$ 9779 million, UI: 9717–9841) and South Africa (INT$ 6744 million, UI: 6676–6811). Conclusions The global economic burden of schistosomiasis remains substantial and is inequitably distributed among countries and regions. Our study highlights the need for increased investment and global collaborative efforts to control schistosomiasis and its associated health and economic burdens. By advancing the elimination of schistosomiasis, substantial economic returns can be achieved. Graphical Abstract